Gut Antibody Deficiency in a Mouse Model of CVID Results in Spontaneous Development of a Gluten-Sensitive Enteropathy - Mohammed, Ahmed Dawood; Khan, Md. A. Wadud; Chatzistamou, Ioulia; Chamseddine, Douja; Williams-Kang, Katie; Perry, Mason; Enos, Reilly; Murphy, Angela; Gomez, Gregorio; Aladhami, Ahmed; Oskeritzian, Carole A.; Jolly, Amy; et al. (Frontiers in Immunology, 2019)
Primary immunodeficiencies are heritable disorders of immune function. CD19 is a B cell co-receptor important for B cell development, and CD19 deficiency is a known genetic risk factor for a rare form of primary immunodeficiency known as 'common variable immunodeficiency' (CVID); an antibody deficiency resulting in low levels of serum IgG and IgA. Enteropathies are commonly observed in CVID patients but the underlying reason for this is undefined. Here, we utilize CD19-/- mice as a model of CVID to test the hypothesis that antibody deficiency negatively impacts gut physiology under steady-state conditions. As anticipated, immune phenotyping experiments demonstrate that CD19-/- mice develop a severe B cell deficiency in gut-associated lymphoid tissues that result in significant reductions to antibody concentrations in the gut lumen. Antibody deficiency was associated with defective anti-commensal IgA responses and the outgrowth of anaerobic bacteria in the gut. Expansion of anaerobic bacteria coincides with the development of a chronic inflammatory condition in the gut of CD19-/- mice that results in an intestinal malabsorption characterized by defects in lipid metabolism and transport. Administration of the antibiotic metronidazole to target anaerobic members of the microbiota rescues mice from disease indicating that intestinal malabsorption is a microbiota-dependent phenomenon. Finally, intestinal malabsorption in CD19-/- mice is a gluten-sensitive enteropathy as exposure to a gluten-free diet also significantly reduces disease severity in CD19-/- mice. Collectively, these results support an effect of antibody deficiency on steady-state gut physiology that compliment emerging data from human studies linking IgA deficiency with non-infectious complications associated with CVID. They also demonstrate that CD19-/- mice are a useful model for studying the role of B cell deficiency and gut dysbiosis on gluten sensitive enteropathies; a rapidly emerging group of diseases in humans with an unknown etiology.